ĐẶC ĐIỂM CẤU TRÚC ĐỘ DẪN ĐIỆN VÀ MỐI QUAN HỆ VỚI DỊ THƯỜNG ĐỊA NHIỆT Ở ĐỚI ĐỨT GÃY SÔNG HỒNG - Tuyến, Đoàn Văn; Toàn, Đinh Văn (Vietnam Journal of Earth Sciences, 2011)
Structural features of Electrical conductivity and its relation to anomaly of geothermal heat flow in the Red River Fault zone On the Red River plain, anomalies of geothermal heat flows are high enough like as in rift zones, many geothermal hot water sources are distributing largely in the region. It possibly related to the deep activities in the low crust of the Earth. In the 1996, the Institute of Geological Sciences (Vietnam Academy of Science and Technology) under cooperation with the Paris Institute of Physic of the Earth (France) were conducted the survey by magnetotelluric soundings (MTS) for studying deep structures of the Red River Fault zone (RRFZ) in the region. The paper presents results of data re-interpretation of 8 MTS distributing along the profile about 75km in length, started from Luong Son Village (SW site) going through Hanoi City and ended in Bac Ninh town (NE site), perpendicular crossing the main structures of RRFZ. Received results are 2D structural cross-section to 100km depth, reflecting features with high electrical conductivity of Red River - Chay River subzone and Lo River fault crossing the “crystallized” surface and Moho discontinuity. One anomaly structure of high electrical conductivity is determined under the Red River - Chay River subzone at the depth 90km. It is permitting to suggest possibly the presence of one anomaly of high temperature relating to the “intrusion” of mantle here. By analyzing the features of the high electrical conductivity structures caused by fracture and temperature factors in the crust and mantle, it is allow to explain that, the anomaly of geothermal heat flow and geothermal hot water sources in Red River plain are supported heat from high temperature mantle sources under the Red River - Chay River subzone.